Submarine Channel Mouth Settings: Processes, Geomorphology, and Deposits - Hodgson, David M.; Peakall, Jeff; Maier, Katherine L. (Frontiers in Earth Science, 2022)
Observations from the modern seafloor that suggest turbidity currents tend to erode as they lose channel-levee confinement, rather than decelerating and depositing their sediment load, has driven investigations into sediment gravity flow behaviour at the mouth of submarine channels. Commonly, channel mouth settings coincide with areas of gradient change and play a vital role in the transfer of sediment through deep-water systems. Channel mouth settings are widely referred to as the submarine channel-lobe transition zone (CLTZ) where well-defined channel-levees are separated from well-defined lobes, and are associated with an assemblage of erosional and depositional bedforms (e.g., scours and scour fields, sediment waves, incipient channels). However, our review of modern seafloor studies suggests that a wide range of channel mouth configurations exist. These include traditional CLTZs, plunge pools, and distinctive long and flared tracts between channels and lobes, which we recognise with the new term channel mouth expansion zones (CMEZs). In order to understand the morphodynamic differences between types of channel mouth settings, we review insights from physical experiments that have focussed on understanding changes in process behaviour as flows exit channels. We integrate field observations and numerical modelling that offer insight into flow behaviours in channel mouth settings. From this analysis, we propose four types of channel mouth setting: i) supercritical CMEZs on slopes; ii) plunge pools at steep slope breaks with high incoming supercritical Froude numbers; iii) CLTZs with arrays of hydraulic jumps at slope breaks with incoming supercritical Froude numbers closer to unity; and, iv) subcritical CLTZs associated with slope breaks and/or flow expansion. Identification of the stratigraphic record of channel mouth settings is complicated by the propagation, and avulsion, of channels. Nonetheless, recent studies from ancient outcrop and subsurface systems have highlighted the dynamic evolution of interpreted CLTZs, which range from composite erosion surfaces, to metres to tens of metres thick stratigraphic records. We propose that some examples be reconsidered as exhumed CMEZs.